Wireless Battery Management System for Military Unmanned Vehicles - Pham, N. N.; Leuchter, J.; Dong, H. Q. (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2022)
This paper introduces a Battery Management System (BMS) for Military Unmanned Vehicles, which uses multi-cell battery packs. The designed BMS is composed of slave modules and a master module. Each slave module is in charge of managing the state of one battery, include flowing current, voltage of battery, voltage of each cell, temperature of battery. From these obtained data, each module can predict the State of Charge (SoC) of connected battery. All slave modules are interconnected to the master module via Wireless Communication Protocol such as Wi-Fi, Bluetooth, or ESP-NOW. The master module will save all the received data to a microSD card, and if required, send these data to a workstation. These data are useful to predict the operation range of the vehicle, which is very important for decision the tactic of using. The designed BMS was verified in various applications in University of Defence in Brno.
Keywords: Battery Management System; Military Unmanned Vehicle; Wireless Communication Protocol